Evaluation Of The Application Of First Aid In Accidents (P3k) At PT.X - Rohmah, Mazidatur; Sunaryo, Merry; Pratama, Muchammad Rafi Wahyu; Mubarok, Naufal Al Faridzi; Sahri, Moch (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2023)
Potential hazards in the workplace can result in work accidents and occupational diseases. One of the controls against work accidents is the availability of first aid kits in the workplace. The type of research used is descriptive observational research using cross sectional study research. This research was conducted at PT X in June 2023. The population of this study were 24 workers at PT. X. Data collection using observation sheets (Checklist Sheets) guided by the Regulation of the Minister of Manpower and Transmigration of the Republic of Indonesia No. 15 of 2008 concerning first aid in accidents in the workplace. The requirements for first aid officers at PT X are still not implemented, there should be 1 first aid officer at PT X because it has more than 24 workers and has a mild risk of work accidents in accordance with the regulations set by the Minister of Manpower and Transmigration No. 15 of 2008. Completeness of t h e first aid facility, such as the first aid room at PT X is not available, the contents of the first aid box do not meet the standards, the placement of the first aid box is not clearly visible, the red first aid symbol should be green. There is no means of transportation (ambulance) and shower in additional facilities. The implementation of First Aid at PT X is not appropriate. Therefore, it is recommended for the company to conduct socialization to workers, increase maintenance and create a logbook to monitor first aid kits and their contents, add a map to the first aid kit and the contents of the first aid kit. find out the location of the first aid kit at PT X.